Meningkatkan Kualitas Hidup Lansia melalui Edukasi Kesehatan Gigi dan Pentingnya Gigi Tiruan - Ardinansyah, Agus; Amir, Ardin; Prihastari, Lisa; Atmaji, Moch; Nurniza, Nita (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Tooth loss is a common health issue among the elderly and can significantly affect their quality of life. This problem not only impacts chewing function but can also influence psychological and social aspects, such as decreased self-esteem and difficulties in social interactions. According to the 2018 Indonesian Health Research (RISKESDAS), the prevalence of tooth loss among the elderly (aged 65 and above) is high, yet only a small percentage seek dental care or replacement, such as dentures. This community service program aims to improve the quality of life of elderly residents in Kelurahan Cempaka Putih Barat through dental health education and raising awareness about the importance of dentures as a solution for tooth loss. The methods used in this activity included general health screenings (blood sugar, blood pressure, and cholesterol), elderly fitness exercises, proper tooth brushing education, and plaque examination. Additionally, counseling was provided on the importance of maintaining oral health and the benefits of using dentures to enhance quality of life. The results of the program showed an increase in the elderly's knowledge about proper oral care and a greater awareness of the role dentures can play in improving their overall well-being. This activity is expected to encourage the elderly to take better care of their oral health and reduce the negative impacts of tooth loss on their quality of life.